Technology Adaptation as 21st Century Skill among Educators: Understanding the Challenges - Kriti Guleria, Dr. Alka Muddgal, Dr. Meena Bhandari (South Eastern European Journal of Public Health, 2025)
In the 21st century, technology has become an essential tool in education, shaping pedagogical approaches and enhancing learning experiences. However, educators face significant challenges in adapting to technological advancements, impacting their ability to foster critical skills such as digital literacy, collaboration, and problem-solving. This study explores the challenges educators encounter in integrating technology into their teaching practices, with a particular focus on gender differences, teaching experience (in-service vs. pre-service teachers), institutional type, and educational qualifications. Findings indicate that female educators demonstrate higher openness and employ more diverse strategies for technology adoption compared to their male counterparts. Pre-service teachers exhibit greater enthusiasm and motivation than in-service teachers, suggesting that structured training programs play a crucial role in fostering adaptability. Institutional variations reveal that government educators show more reluctance but utilize broader adaptation strategies, whereas private institution educators display greater receptiveness due to institutional support. Additionally, educators with PhDs tend to rely on traditional methods, whereas those with Bachelor’s and Master’s degrees exhibit higher adaptability. These findings highlight the need for targeted professional development programs, policy interventions, and institutional support to bridge technological adaptability gaps among educators. By addressing barriers such as digital infrastructure, resistance to change, and skill gaps, this study contributes to the ongoing discourse on enhancing technology integration in education, ultimately fostering a future-ready teaching workforce.